Calidad de vida en las asociadas de ASOPROMUABA de la parroquia Boyacá cantón Chone - Intriago Vichirel, Luis Antonio (2025)
The research conducted at the Women Beekeepers Agricultural Production Association La Barranca in Boyacá aimed to evaluate the quality of life of its members and its impact on collective well-being. A descriptive methodology was used, applying surveys as the main instrument, along with statistical analysis for data interpretation. The study was carried out in three phases: the first phase involved a situational diagnosis that characterized the members in terms of sociodemographic, economic, and labor-related factors, identifying key elements affecting their quality of life. In the second phase, the data were analyzed to determine the relationship between quality of life indicators and collective well-being. The results showed that access to basic services, financial stability, and working conditions significantly influence their sense of well-being. The third phase consisted of designing an action plan with strategies to improve these aspects, including training programs, strengthened access to financing, and the promotion of cooperative work. Findings revealed that the members face limitations in areas such as financial security, access to healthcare, and recreational opportunities, all of which negatively impact their overall well-being. It is concluded that strengthening the organization, improving access to resources, and enhancing labor conditions can have a positive effect on quality of life and the sustainability of the association, fostering long-term growth and stability.